The Language of Extremism on Social Media: An Examination of Posts, Comments, and Themes on Reddit - Hiaeshutter-Rice, Dan; Hawkins, Ian (Frontiers in Political Science, 2022)
Digital media give the public a voice to discuss or share their thoughts about political and social events. However, these discussions can often include language that contributes to creating toxic or uncivil online environments. Using data from Reddit, we examine the language surrounding three major events in the United States that occurred in 2020 and early 2021 from the comments and posts of 65 communities identified for their focus on extreme content. Our results suggest that social and political events in the U.S. triggered increased hostility in discussions as well as the formation of a set of shared language for describing and articulating information about these major political/social moments. Findings further reveal shifts in language toward more negativity, incivility, and specific language surrounding non-White outgroups. Finally, these shifts in language online were found to be durable and last after the events occurred. Our project identifies that negative language is frequently present on social media and is not necessarily exclusive to one group, topic, or real-world event. We discuss the implications of language as a powerful tool to engage, recruit, and radicalize those within communities online.